INDONESIAN SUSTAINABLE PALM OIL (ISPO), A WAY TO REACH THE EUROPEAN UNION RENEWABLE ENERGY DIRECTIVE (EU RED) 2009 AND BOOSTING INDONESIAN PALM OIL MARKET TO EUROPEAN UNION (EU) 2009-2014 - Ariance Valentina Hia; Natasya Kusumawardani (President University, 2016)
Renewable energy is expected to support the sustainable development whether in terms of environment itself, or in economic and social. Biofuel as the product of palm oil is one of the renewable energy sources that can answer the problems that caused by fossils fuels such as greenhouse gases (GHG), limited availability, and the volatile price. Biofuels is environmentally and economically friendly that can help to reduce GHG, affordable, and renewable which then make it sustainable. Indonesia as the biggest producer of palm oil becomes the importer of biofuels for other countries especially European Union (EU) as one of biggest importer of palm oil from Indonesia. EU has big concern on sustainable energy which provides European Union Renewable Energy Directive (EU RED) 2009 for a sustainable palm oil. Indonesia gave response in creating government regulation of Indonesian Sustaianble Palm Oil (ISPO). Question raised: How did the Government Regulation from Minister of Agriculture No. 19/PERMENTAN/OT.140/3/2011 about ISPO adjusts the EU-RED biofuels sustainable criteria while protecting the Indonesian palm oil export activities to EU (2009-2014)? The result of this study is that the principles and criterion consist in the ISPO meet the criterion from biofuels sustainable regulated in EU RED. It has the same goals of sustainable criteria for palm oil. In addition, the ISPO gave great impact for the demand of EU for Indonesian palm oil. Thus, the ISPO has big potential to reach the goals of sustainable palm oil and protecting Palm oil market to Europe in the future.